Downregulated Gene Expression Spectrum and Immune Responses Changed During the Disease Progression in Patients With COVID-19. (20th April 2020) - Ouyang, Yabo; Yin, Jiming; Wang, Wenjing; Shi, Hongbo; Shi, Ying; Xu, Bin; Qiao, Luxin; Feng, Yingmei; Pang, Lijun; Wei, Feili; Guo, Xianghua; Jin, Ronghua; et al.
Abstract: Background: The World Health Organization characterizes novel coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), as a pandemic. Here, we investigated the clinical, cytokine levels; T-cell proportion; and related gene expression occurring in patients with COVID-19 on admission and after initial treatment. Methods: Eleven patients diagnosed with COVID-19 with similar initial treatment regimens were enrolled in the hospital. Plasma cytokine, peripheral T cell proportions, and microfluidic quantitative polymerase chain reaction analyses for gene expression were conducted. Results: Five patients with mild and 6 with severe disease were included. Cough and fever were the primary symptoms in the 11 COVID-19 cases. Older age, higher neutrophil count, and higher C-reactive protein levels were found in severe cases. IL-10 level significantly varied with disease progression and treatment. Decreased T-cell proportions were observed in patients with COVID-19, especially in severe cases, and all were returned to normal in patients with mild disease after initial treatment, but only CD4 + T cells returned to normal in severe cases. The number of differentially expressed genes (DEGs) increased with the disease progression, and decreased after initial treatment. All downregulated DEGs in severe cases mainly involved Th17-cell differentiation, cytokine-mediated signaling pathways, and T-cell activation. After initial treatment in severe cases, MAP2K7 and SOS1 were upregulated relative to that on admission. Conclusions: Our findings show that a decreased T-cell proportion with downregulated gene expression related to T-cell activation and differentiation occurred in patients with severe COVID-19, which may help to provide effective treatment strategies for COVID-19. Abstract : Suppressed T-cell immune response and decreased T cells occurred in patients with COVID-19 related to downregulated gene expression involved in T-cell activation and differentiation, especially in severe disease, against SARS-CoV-2 infection and at the early period of treatment.